Vision measurement method to promote calibration precision of capacitance gradient in micro-force measurement system. (2016) - Sun, Peiyuan; Cai, Xue; Song, Le; Zheng, Yelong; Zhao, Meirong
The micro-force measurement system based on electrostatic force using a pair of precision coaxial cylindrical electrodes as a force generator is proposed. However, there is axes deviation between the inner and outer electrodes inevitably, which can cause a change of the capacitance value. In this paper, a system is designed to measure and adjust the coaxiality of the coaxial cylindrical electrodes. After that the multidimensional adjustment stage is used to adjust the inner and outer electrodes to make them coaxial, it has a precision of 5 µm to adjust the eccentric error, and 0.030° to adjust the tilt error. A reasonable scheme is designed to calibrate the capacitance gradient, the experiment results show that after adjusting the inner and outer electrodes coaxial, the relative standard deviation in multiple measurements can be less than one over a thousand. With this measurement and adjustment scheme, the capacitance gradient value can get a good repeatability.